2018
DOI: 10.1371/journal.pone.0201060
|View full text |Cite
|
Sign up to set email alerts
|

Efficient recovery of recombinant CRM197 expressed as inclusion bodies in E.coli

Abstract: CRM197, which retains the same inflammatory and immune-stimulant properties as diphtheria toxin but with reduced toxicity, has been used as a safe carrier in conjugated vaccines. Expression of recombinant CRM197 in E. coli is limited due to formation of inclusion bodies. Soluble expression attempts in Bacillus subtilis, P. fluorescens, Pichia pastoris, and E. coli were partially unsuccessful or did not generate yields sufficient for industrial scale production. Multiple approaches have been attempted to produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 42 publications
0
17
0
1
Order By: Relevance
“…Park and co-workers showed that the presence of this purification tag did not disrupt CRM197 folding or activity. 11 The constructed plasmid was transformed into BL21 (DE3) cells (Lucigen) and plated onto LB media supplemented with ampicillin. A single colony was picked and cultured overnight at 37 °C/200 rpm in 2 mL of LB media supplemented with ampicillin.…”
Section: Methodsmentioning
confidence: 99%
“…Park and co-workers showed that the presence of this purification tag did not disrupt CRM197 folding or activity. 11 The constructed plasmid was transformed into BL21 (DE3) cells (Lucigen) and plated onto LB media supplemented with ampicillin. A single colony was picked and cultured overnight at 37 °C/200 rpm in 2 mL of LB media supplemented with ampicillin.…”
Section: Methodsmentioning
confidence: 99%
“…Both classical and non-classical IBs contain relatively pure and intact recombinant proteins, and several approaches have been reported to recover biologically active proteins from these aggregated forms. Usually, during an in vitro refolding procedure, IBs are denatured by dissolving with a high or mild concentration of chaotropic denaturants such as urea, guanidine hydrochloride (GdnHCl) [ 16 ], or alternately with non-ionic or ionic detergents, such as Triton X-100, N-lauroylsarcosine, dimethylsulfoxide (DMSO) and a low percentage (~5%) of n-propanol [ 17 ]. In addition, dithiothreitol (DTT) or 2-mercaptoethanol was added to reduce undesirable inter- and/or intra-molecular disulfide bonds [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…High concentration of chaotropic agent results in complete denaturation of insoluble IBs which are further subjected to a single refolding step to recover soluble protein [16]. Alternatively, soluble protein can also be recovered directly from non-classical IBs by using non-denaturing solubilizing agents such as N -lauroyl sarcosine, dimethylsulfoxide (DMSO) and low percentage (~ 5%) of n -propanol [7, 17, 18]. Several studies have mentioned earlier that the recovery yield of soluble protein from bacterial IBs depends on its nature and the strength of denaturing agents which are applied during the solubilization process [7, 19].…”
Section: Introductionmentioning
confidence: 99%